Território do milho crioulo: a propriedade intelectual coletiva e o melhoramento genético como estratégia de reprodução social - Campos, Antônio Valmor de (2018)
Seeds are structures resulting from genetic improvement, occurring in nature itself or by human intervention. This thesis aims to demonstrate that farmers, from the territorialization of traditional knowledge and practices improve, each crop, the creole seeds, adding to the accumulations of the past generations, some improvement contributions. Therefore, these farmers are researchers, who use their own crops as a laboratory to carry out the experiments. They hold intellectual rights to the improvement they make. The recognition of this right must be differentiated, with collective characteristics providing the improvements so that other farmers can continue the evolution. In order to base these reflections, the present research was carried out, which deals with traditional knowledge and territorial practices, intergenerational visions and their territorialization, which provide for the improvement of creole seeds. It contains an analysis of the Brazilian legislation related to seeds and protection of cultivars, with an eye on international agreements that deal with the protection of breeders 'and breeders' rights and the internal reflexes in the laws that govern intellectual property in the patenting of living beings or their parts. Considerations are also made about the legislation of other countries regarding the protection of farmers who improve and conserve their own seeds. Field research was conducted through interviews with twelve farmers distributed in the different territories of the Creole corn in the State of Santa Catarina, where they perform improvements in the Creole seeds. Also interviewed, with semi-structured questionnaires, seven technicians, who have links with the better farmers. After analyzing the comparative interviews with Brazilian and international legislation, the need was for Brazil to have specific legislation that recognizes the contribution of the farmers in the improvement of the native seeds and assures them the inherent rights, without creating obstacles for the process to continue , in the molds of past generations. Alternatives were presented for this protection model, with a patent applied to free software, which allows access to all information necessary to continue the aggregation of improvements.